Simplifying
x2 + 3x = 25
Reorder the terms:
3x + x2 = 25
Solving
3x + x2 = 25
Solving for variable 'x'.
Reorder the terms:
-25 + 3x + x2 = 25 + -25
Combine like terms: 25 + -25 = 0
-25 + 3x + x2 = 0
Begin completing the square.
Move the constant term to the right:
Add '25' to each side of the equation.
-25 + 3x + 25 + x2 = 0 + 25
Reorder the terms:
-25 + 25 + 3x + x2 = 0 + 25
Combine like terms: -25 + 25 = 0
0 + 3x + x2 = 0 + 25
3x + x2 = 0 + 25
Combine like terms: 0 + 25 = 25
3x + x2 = 25
The x term is 3x.
Take half its coefficient (1.5).
Square it (2.25) and add it to both sides.
Add '2.25' to each side of the equation.
3x + 2.25 + x2 = 25 + 2.25
Reorder the terms:
2.25 + 3x + x2 = 25 + 2.25
Combine like terms: 25 + 2.25 = 27.25
2.25 + 3x + x2 = 27.25
Factor a perfect square on the left side:
(x + 1.5)(x + 1.5) = 27.25
Calculate the square root of the right side: 5.220153254
Break this problem into two subproblems by setting
(x + 1.5) equal to 5.220153254 and -5.220153254.